Morphoelastic rods III: Differential growth and curvature generation in elastic filaments - Moulton, DE; Lessinnes, T; Goriely, A (Elsevier, 2020)
In many growing filamentary structures such as neurons, roots, and stems, the intrinsic shapes and material response is produced by differential growth of the tissue. Therefore, a key problem is to link the growth field at the microscopic level to the macroscopic shape and properties of the filaments. Here, starting with a morphoelastic tubular structure and assuming a form of the growth tensor, we use dimensional reduction to obtain the overall curvature, torsion, and material parameters of a growing filament. Various examples of curvature and torsion generation are given and the impact of residual stress on the generation of curvature is demonstrated.